Partycypacja pracownicza w polskiej prywatyzacji - Suwalski, Andrzej (Wydział Prawa i Administracji UAM, 1996)
The article discussed the aspect of ownership transformations in Poland related with the participation of the personnel of state enterprises. The demonstration of the problem contains a presentation of its fundamental conditions, the models extant in modern capitalism and a discussion of the place of labour participation and the main, relevant controversial issues in regulating the transformation process. The solutions adopted and the practice of their implementation have a considerable impact on the shaping of the new ownership arrangement and the ensuing efficiency in firm management. They also influence the new labour relations arrangement, which is intended to support the development of negotiatory ways of resolving collective work disputes.
Labour participation in Polish privatization